Factors Regulating the Relationship Between Total and Size-Fractionated Chlorophyll-a in Coastal Waters of the Red Sea - Brewin, Robert J. W.; Morán, Xosé Anxelu G.; Raitsos, Dionysios E.; Gittings, John A.; Calleja, Maria Ll.; Viegas, Miguel; Ansari, Mohd I.; Al-Otaibi, Najwa; Huete-Stauffer, Tamara M.; Hoteit, Ibrahim (Frontiers in Microbiology, 2019)
Phytoplankton biomass and size structure are recognised as key ecological indicators. With the aim to quantify the relationship between these two ecological indicators in tropical waters and understand controlling factors, we analysed the total chlorophyll-a concentration, a measure of phytoplankton biomass, and its partitioning into three size classes of phytoplankton, using a series of observations collected at coastal sites in the central Red Sea. Over a period of 4 years, measurements of flow cytometry, size-fractionated chlorophyll-a concentration, and physical-chemical variables were collected near Thuwal in Saudi Arabia. We fitted a three-component model to the size-fractionated chlorophyll-a data to quantify the relationship between total chlorophyll and that in three size classes of phytoplankton (pico-, nano- and micro-phytoplankton). The model has an advantage over other more empirical methods in that its parameters are interpretable, expressed as the maximum chlorophyll-a concentration of small phytoplankton (pico- and combined pico-nanophytoplankton, $C^m_p$ and $C^m_{p,n}$ respectively) and the fractional contribution of these two size classes to total chlorophyll-a as it tends to zero ($D_p$ and $D_{p,n}$). Residuals between the model and the data (model minus data) were compared with a range of other environmental variables available in the dataset. Residuals in pico- and combined pico-nanophytoplankton fractions of total chlorophyll-a were significantly correlated with water temperature (positively) and picoeukaryote cell number (negatively). We conducted a running fit of the model with increasing temperature and found a negative relationship between temperature and parameters $C^m_p$ and $C^m_{p,n}$ and a positive relationship between temperature and parameters $D_p$ and $D_{p,n}$. By harnessing the relative red fluorescence of the flow cytometric data, we show that picoeukaryotes, which are higher in cell number in winter (cold) than summer (warm), contain higher chlorophyll per cell than other picophytoplankton and are slightly larger in size, possibly explaining the temperature shift in model parameters, though further evidence is needed to substantiate this finding. Our results emphasize the importance of knowing the water temperature and taxonomic composition of phytoplankton within each size class when understanding their relative contribution to total chlorophyll. Furthermore, our results have implications for the development of algorithms for inferring size-fractionated chlorophyll from satellite data.